PEMILIHAN KARIER BERDASARKAN GAYA BELAJAR MODEL “KOLB” PADA SISWA CERDAS ISTIMEWA KELAS 12 CERDAS ISTIMEWA BAKAT ISTIMEWA SMAN 1 WONOSARI - Alfiana Rohali; Rochmat Wahab (JPK (Jurnal Pendidikan Khusus), 2019)
The aim of this study was to describe of gifted student’s learning style based on the Kolb model learning style in the form of divergers, assimilators, convergers and accommodators and career choice among gifted students. The aspects examined in this study was career choice based on the learning style of the "KOLB" model. The subjects of the study were gifted students in3rdgrade class of senior high school. The data collection of the study used a non-test technique in the form of a questionnaire. The method of data analysis uses descriptive statistical analysis. The results showed that 10 students had an assimilation learning style, 7 students had diverger learning styles, 6 students had learning styles and no students had an accommodating learning style. The results of the study show that the majority of sgifted students are able to make career selection decisions that are congruent with the learning style even though the interests of the career fields of gifted students are still very diverse.